Projected dryness/wetness pattern and influence factors in China under the CMIP6 scenarios for 2021–2100 - Jing Yang; Changxiu Cheng; Zheng Wang; Ping Liu (Geomatics, Natural Hazards & Risk)
Analyzing spatiotemporal patterns of dryness/wetness is important for measures and strategy development for the resulting disasters. This research explores projected dryness/wetness patterns and influence factors in China under two Shared Socioeconomic Pathway (SSP)-based scenarios (SSP245 and SSP585). The dryness/wetness is evaluated by a non-parameter Standardized Precipitation Evapotranspiration Index, and the influence is analyzed by the GeoDetector method. The result shows that under SSP245, dryness is more likely to increase in autumn. It is primarily located in North-China, South-China, and Middle-lower Yangtze in summer and autumn and in South-China and Huang-Huai-Hai in other seasons. Wetness is more likely to be enhanced in winter, and simultaneous precipitation has more influence, especially in semiarid regions. Under SSP585, the dryness is enhanced throughout China except in winter, and the wetness is enhanced except in autumn. The enhanced wetness in spring and winter is located in North-China and in summer in Southwest China. Temperature has a greater influence in spring and autumn, and precipitation has a greater influence in winter on dryness. The interaction influence is enhanced in almost all regions and seasons under two scenarios. The results could be useful for land managers to develop strategies and mitigate the effects of climate change.